Inflammation and gastrointestinal cancers - Jankowski, Janusz A. Z. (Recent results in cancer research, 2011)
Inflammation in gastrointestinal mucosa is the single most common pathway for GI cancer. This book examines the relation between inflammation and GI cancer, from basic to translational science, which is helping optimize clinical management strategies.